HINT1 suppression protects against age-related cardiac dysfunction by enhancing mitochondrial biogenesis - Michio Sato; Tsuyoshi Kadomatsu; Jun Morinaga; Yuya Kinoshita; Daisuke Torigoe; Haruki Horiguchi; Sumio Ohtsuki; Shuji Yamamura; Ryoko Kusaba; Takanori Yamaguchi; Goro Yoshioka; Kimi Araki; et al. (Molecular Metabolism)
Objective: Cardiac function declines with age, impairing exercise tolerance and negatively impacting healthy aging. However, mechanisms driving age-related declines in cardiac function are not fully understood. Methods: We examined mechanisms underlying age-related cardiac dysfunction using 3- and 24-month-old wild-type mice fed ad libitum or 24-month-old wild-type mice subjected to 70% calorie restriction (CR) starting at 2-month-old. In addition, cardiac aging phenotypes and mitochondrial biogenesis were also analyzed in 25-month-old cardiac-specific Hint1 knockout mice, 24-month-old CAG-Caren Tg mice, and 24-month-old wild-type mice injected with AAV6-Caren. Results: We observed inactivation of mitochondrial biogenesis in hearts of aged mice. We also showed that activity of the BAF chromatin remodeling complex is repressed by HINT1, whose expression in heart increases with age, leading to decreased transcription of Tfam, which promotes mitochondrial biogenesis. Interestingly, CR not only suppressed age-related declines in cardiac function and mitochondrial biogenesis but blocked concomitant increases in cardiac HINT1 protein levels and maintained Tfam transcription. Furthermore, expression of the lncRNA Caren, which inhibits Hint1 mRNA translation, decreased with age in heart, and CR suppressed this effect. Finally, decreased HINT1 expression due to Caren overexpression antagonized age-related declines in mitochondrial biogenesis, ameliorating age-related cardiac dysfunction, exercise intolerance, and exercise-induced cardiac damage and subsequent death of mice. Conclusion: Our findings suggest that mitochondrial biogenesis in cardiomyocytes decreases with age and could underlie cardiac dysfunction, and that the Caren-HINT1-mitochondrial biogenesis axis may constitute a mechanism linking CR to resistance to cardiac aging. We also show that ameliorating declines in mitochondrial biogenesis in cardiomyocytes could counteract age-related declines in cardiac function, and that this strategy may improve exercise tolerance and extend so-called ''healthy life span''.